ANALISIS DAMPAK GAME ONLINE FREE FIRE TERHADAP PERILAKU PROKRASTINASI PADA SISWA KELAS TINGGI - Muhammad Aldi Febri Hernanda; Diana Endah Handayani; Henry Januar Saputra (Jurnal Binagogik, 2026)
The development of digital technology has increased the use of online games among elementary school students. However, excessive use may disrupt time management, learning discipline, and academic responsibility, as well as encourage academic procrastination. This study aims to analyze the impact of the online game Free Fire on academic procrastination and identify the relationship between gaming intensity and the learning behavior of upper-grade students at SDN Guntur 2, Demak Regency. This study employed a descriptive qualitative approach involving 21 students from Grades IV, V, and VI who played Free Fire. Data were collected through questionnaires, observations, interviews with teachers and parents, and documentation. Data validity was examined using source and technique triangulation, while data analysis involved data reduction, data presentation, and conclusion drawing. The results showed that 80% of students reduced their study time because of playing Free Fire, while 71% tended to postpone completing school assignments. The forms of procrastination identified included delaying homework, studying shortly before examinations, completing assignments near deadlines, difficulty managing time, and reduced concentration during learning activities. Students with high gaming intensity tended to experience greater difficulty balancing study, play, and rest time than students with low gaming intensity. These findings indicate that uncontrolled use of Free Fire is associated with increased academic procrastination. Therefore, parental supervision, teacher guidance, and restrictions on gaming time are necessary to prevent online gaming activities from interfering with students’ academic responsibilities.